Behavior of high strength concrete (M-60) subjected to elevated temperatures - Rao, V. Srinivasa; Rao, K. Srinivasa; Rambabu, K. (Journal of Structural Engineering, 2024)
The concrete being predominant construction material due to its higher compressive strength and enhanced durability is extensively utilized all over the world. The High Strength Concrete (HSC) is achieved with state-of-the art additives like mineral and chemical admixtures to the traditional concrete. Though much attention had been bestowed over the performance of concrete under room temperature conditions, the experimental study on behavior of slag concrete subjected to elevated temperature is gaining momentum. As far as the scope of present study is concerned, it is proposed to study the mechanical properties of high strength slag cement concrete (M-60) subjected to high temperature from 100 to 500°C with 1, 2 and 3 hour duration apart from room temperature. The residual compressive strength at 100°C increased for 1 and 2 hour exposure durations whereas for 3 hour exposure duration, it continued to fall from 100 to 500°C. Ultimately the residual strength fallen below 70% for 3 hour exposure at 500°C. Similar descending trends are observed for flexural and split tensile strengths with the former getting reduced to about 60% and the latter to below 60% at 500°C temperature for 3 hour exposure duration. Among the 3 parameters of Compressive, Flexural and Split tensile strength, the loss in residual split tensile strength is on higher side followed by flexural tensile strength and compressive strength resembling the inherent characteristics of higher compressive strength of concrete even after exposed to high temperatures.